Marketing Communication Strategies in Room Sales Hotel Harris Suites FX Sudirman Jakarta - Murhadi; Salsabila Yasmin Wijaya (International Journal of Travel, Hospitality and Events, 2025)
Purpose: This study analyzes marketing communication strategies in increasing hotel room sales. Marketing communication strategies used include digital marketing, package promotion, strategic partnerships, loyalty programs, service improvements, and community-based approaches. This study aims to find out effective marketing communication strategies to be applied in the sale of hotel rooms. Research Methode: The research method uses a descriptive qualitative approach with marketing informants and guests staying at the Harris Suites FX Jakarta hotel as well as data collection techniques through interviews with informants and observation activities. Result and Discussion:The findings of this study show that the implementation of an effective marketing communication strategy greatly affects the sales rate of rooms. The use of social media such as Instagram, TikTok, and websites has proven to be effective in reaching out to potential guests widely and increasing the attraction of guests to stay at hotels. An integrated and responsive communication approach to technological developments has strengthened the brand image and significantly expanded the hotel's market share. Implication: This research can be used as a study material for Hotel Haris Suites FX Jakarta in planning and implementing effective communication strategies to increase room sales, face competition with competitors, and seize market opportunities in the hotel industry.